Northwest history. Mining. Production. 1920-10-08 (1920)
Friend company mines more ore. - Output of beaver creek property shows good increase. - An improvement in the amount of ore coming in at the present time in the Friend Mining company's property in the Beaver creek section of the Coeur d'Alenes was reported this week.